Penerapan E-System Perpajakan dan Tingkat Pemahaman Terhadap Kepuasan Wajib Pajak Pribadi di Kota Makassar - Dahniyar Daud; Musdalifah Musdalifah (Al-Buhuts, 2019)
The purpose of this study was to determine the application of e-taxation systems and the level of understanding of taxation on the level of satisfaction of personal taxpayers in Makassar. This study uses primary data obtained from questionnaires distributed to all taxpayers in Makassar. The population is the taxpayer of individuals registered at the Tax Service Office in the city of Makassar totaling 205,681 taxpayers, while the sample taken amounted to 100 respondents. The data analysis method uses multiple linear regression techniques. The results of this study indicate where the proposed hypothesis is accepted because it shows the results of a positive and significant hypothesis test. This means that the effect of applying the e-taxation system and the level of understanding has a significant positive effect on the level of taxpayer satisfaction